Laboratory findings in COVID-19 - alterations of hematological, immunological, biochemical, hormonal and other lab panels: a narrative review - Yousef Rasmi; Lucas Paulo Jacinto Saavedra; Matei-Alexandru Cozma; Heba A.S. El-Nashar; Shaza H. Aly; Nouran M. Fahmy; Omayma A. Eldahshan; Mohamed El-Shazly; Elena-Codruța Dobrică; Hamed Kord-Varkaneh; Camelia Cristina Diaconu; Mihnea-Alexandru Găman (Journal of Mind and Medical Sciences)
Up to the present date, according to the official reports of the World Health Organization (WHO), 205,338,159 patients have been confirmed with the coronavirus disease (COVID-19) and 4,333,094 have died as a consequence of this infectious disorder. The majority of COVID-19 patients will develop hematological, biochemical, immunological, hormonal and other complex alterations of their laboratory data which may be diagnosed using different biomarkers. In this paper, we review the alterations of the hematology, immunology, biochemistry, hormonal and other laboratory panels discovered in the subjects diagnosed with SARS-CoV-2 infection, based on the available data in the literature.